Budidaya Sayur secara Hidroponik dan Ikan Lele (Mix Farming) dalam Mempertahankan Ketahanan Pangan Keluarga di Desa Kajeksan - Suyono; Zahra Maulida; Della Oktaviani Putri; Nadira Aulia Rizqiana Putri; Windi Yuni Astutik; Ivan Adi Susanto; Nauval Rahmad Salam (Jurnal Suara Pengabdian 45, 2025)
The KKN Program of Universitas PGRI Adi Buana Surabaya for the 2024–2025 period in Kajeksan Village, Sidoarjo Regency, focuses on the issue of family food security by implementing a mixed farming system based on the use of used goods. This service method uses Participatory Action Research (PAR) through the stages of to know (identifying problems), to understand (socialization of concepts), to plan (design a system from gallons of mineral water), to act (training and assistance in making hydroponics-aquaponic systems, making fish feed from household waste, and natural vitamins), and to change (evaluation and sustainability). As a result, there is an improvement in community skills with the realization of catfish harvest along with optimal kale growth, opening household business opportunities, and creating a sustainable empowerment model through appropriate technology transfer.